Burden of falls associated with low bone density globally, in China and ASEAN countries: 1990–2021 trends and projections to 2035 - Huang, Rui; Teng, Yilin; Wang, Roumei; Tong, Ye; Lei, Ming; Wan, Baicheng; Zong, Shaohui; Zeng, Gaofeng (Frontiers in Medicine, 2025)
BackgroundFalls have become a critical challenge for the global elderly population, posing a serious public health issue. Therefore, this study aims to evaluate the current burden of falls associated with low bone density (LBMD) and analyze its trends from 1990 to 2021 globally, in China, and in ASEAN (Association of Southeast Asian Nations) countries, while also projecting future trends up to 2035.MethodsWe incorporated the Socio-demographic Index (SDI) to assess the influence of developmental levels, employed the estimated annual percent change (EAPC) and joinpoint regression to capture and quantify temporal trends, and applied frontier analysis to evaluate efficiency gaps and the potential for improvement across countries. In addition, we used the Bayesian Age-Period-Cohort (BAPC) model to forecast future disease burden trends.ResultsFrom 1990 to 2021, global deaths from falls due to LBMD increased from 122,143 to 324,557, and disability-adjusted life years (DALYs) increased from 5.02 to 11.34 million. Despite this trend, ASMR remained stable (EAPC = 0.18%) and ASDR declined slightly (EAPC = −0.15%). China and ASEAN countries experienced a rising burden, accounting for 23.29% of deaths and 24.41% of DALYs in 2021. ASMR and ASDR increased with age, peaking in those aged ≥80 years, with older females bearing a higher burden. Frontier analysis identified Cambodia, Vietnam and Myanmar as having the greatest potential for improvement. By 2035, global ASMR and ASDR are projected to decline, though ASDR may show increase in countries such as Cambodia and Thailand.ConclusionThis study integrated joinpoint, frontier, and BAPC analyses, providing new insights into the association between burden of falls and low bone density globally and in China and ASEAN countries. The results indicated that the burden of falls associated with low bone density remains substantial worldwide, in China, and in ASEAN countries, particularly in low-income nations and among individuals aged 80 years and older. Therefore, it is necessary to prioritize fall prevention and bone health strategies, especially in resource-limited settings, while optimizing healthcare resource allocation and strengthening policy interventions to effectively alleviate this global health challenge.